2018
DOI: 10.18632/aging.101391
|View full text |Cite
|
Sign up to set email alerts
|

The role of FSH and TGF-β superfamily in follicle atresia

Abstract: Most of the mammalian follicles undergo a degenerative process called “follicle atresia”. Apoptosis of granulosa cells is the main characteristic of follicle atresia. Follicle stimulating hormone (FSH) and the transforming growth factor β (TGF-β) superfamily have important regulatory functions in this process. FSH activates protein kinase A and cooperating with insulin receptor substrates, it promotes the PI3K/Akt pathway which weakens apoptosis. Both Smad or non-Smad signaling of the transforming growth facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
45
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(46 citation statements)
references
References 135 publications
0
45
1
Order By: Relevance
“…Studies have shown that activated PI3K/AKT pathway is closely related to the occurrence of chondrocyte apoptosis in OA. FSH is associated with the occurrence of various diseases by activating the PI3K/AKT signaling pathway [19][20][21]. For example, elevated FSH activates the PI3K/AKT signaling pathway and promotes the proliferation of ovarian cancer cells [22].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that activated PI3K/AKT pathway is closely related to the occurrence of chondrocyte apoptosis in OA. FSH is associated with the occurrence of various diseases by activating the PI3K/AKT signaling pathway [19][20][21]. For example, elevated FSH activates the PI3K/AKT signaling pathway and promotes the proliferation of ovarian cancer cells [22].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we found that miR-1185-3p targeted CLDN10 and CADM1 and mediated the cell adhesion molecules to regulate ovarian function. Further, the TGF-β signaling pathway is widely involved in functions such as cell proliferation, apoptosis, differentiation, and migration, which affect follicular development, embryonic development, and organ formation [ 80 , 81 ]. BMP7 [ 82 ], BMP5 [ 83 ], FMOD [ 84 ], TGFB2 [ 85 ], BMPR1B [ 86 ], and SMAD7 [ 87 ] are the main genes in this pathway, and they are closely related to granulosa cell development, follicular maturation, and ovulation.…”
Section: Discussionmentioning
confidence: 99%
“…GnRH is a key regulator in the hypothalamic-pituitary-gonadal axis. The GnRH pathway alters follicle growth, secretion and ovulation [ 29 , 61 ]. The ovaries also undergo various biological processes during the oestrous cycle.…”
Section: Discussionmentioning
confidence: 99%